Considering Lesbian, Gay, Transgender, and Bisexual Nominees for the Federal Courts - Carl Tobias (Washington University Law Review, 2012)
In April 2010, President Barack Obama nominated Edward DuMont to the United States Court of Appeals for the Federal Circuit, while more than one and a half years later the nominee withdrew. The aspirant possesses impeccable credentials, having argued eighteen Supreme Court matters and captured a unanimous well qualified American Bar Association (ABA) rating. Despite his immense capabilities, the prospect never received a hearing. Because Edward DuMont is an exceptionally competent uncontroversial individual and would have been the first out gay court of appeals judge, he merited expeditious review. The nominee’s cautionary tale illuminates how excessive Senate partisanship deprived the appellate bench of a remarkable jurist.
Keywords: supreme court; Edward DuMont; gay; lesbian; transgender; bi-sexual; nominees; federal courts